Legal Implications of the Job Creation Law on the Protection of Community Land Rights in National Strategic Areas - Damayanti, Ditta Dwi; Wahanisa, Rofi; Fidiyani, Rini (Journal of Law, Politic and Humanities, 2025)
The Job Creation Law (Law No. 11 of 2020) as a national strategic policy has sparked controversy, particularly concerning the protection of land rights for indigenous peoples and vulnerable groups. This research is grounded in the concern that the law shifts the orientation of agrarian policy from a social justice paradigm toward investment acceleration, potentially neglecting constitutional community rights. This study aims to critically examine the Job Creation Law and assess the relevance of international legal principles—especially Free, Prior, and Informed Consent (FPIC) under the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP)—in safeguarding land rights in Indonesia. Using a library research method and a critical-juridical approach, this study analyzes national legal provisions, international norms, and comparative agrarian regulations in other countries. The findings indicate that the Job Creation Law does not sufficiently incorporate the FPIC principle, weakening the bargaining power of indigenous and local communities in land acquisition for national projects. Furthermore, the lack of an independent oversight mechanism and an effective agrarian dispute resolution system undermines legal protection. Comparative analysis highlights the need to recognize collective rights and community participation. In conclusion, the law should be revised and harmonized with international legal standards to strengthen community rights through inclusive mechanisms and independent institutions